Metabolic dynamics of secondary metabolites in Arabica coffee (Coffea arabica): From biosynthesis to post-harvest transformations - Dwitama, Kamilrashid Hadi; Maxiselly, Yudithia; Suherman, Cucu; Rosniawaty, Santi (Universitas Padjadjaran, 2026)
Coffee (Coffea arabica) is a globally significant beverage whose sensory profile and physiological effects derive from a complex matrix of secondary metabolites. This review presents a comprehensive